Hasil Belajar Peserta Didik yang Dibelajarkan dengan Metode Question Student Have dan Learning Starts With A Question pada Pembelajaran Biologi Materi Sistem Gerak Kelas XI SMA Negeri 3 Bone - Novira, Aulya; Lodang, Hamka; Muis, Abd (Universitas Negeri Makassar, 2022)
Abstract. This study aims to determine the comparison of learning outcomes between students who are taught by applying the Question Student Have (QSH) learning method with the Learning Start With A Question (LSQ) learning method on the movement system material for class XI SMA Negeri 3 Bone. The subjects of this study were students of class XI MIPA SMA Negeri 3 Bone in the 2020/2021 academic year, which consisted of seven study groups (rombel). The sample of this study was class XI MIPA 1 and XI MIPA 2 SMA Negeri 3 Bone which were selected according to the purpose of this study (purposive sampling). The design of this study was a pretest-posttest comparison group design. Measuring learning outcomes by providing learning outcomes tests. The average learning outcome of students taught by the QSH method is 23.11, while the average learning outcome of students taught by the LSQ method is 31.89. The results of statistical tests using the Mann Whitney Test analysis method were obtained by Asymp.sig. (2-tailed) = 0.04 < 0.05, so it is said that there are differences in biology learning outcomes between students using the Problem Learning method and the Learning Beginning with Problem method on the motion system material, where LSQ is better applied than QSH.Keywords: student have question, learning starts with a question, learning outcome